Past, present and future of the ecosystem services provided by cetacean carcasses - Quaggiotto, M. Martina (2022)
Ecosystem services associated with cetacean strandings have been altered by humans through exploitation of wild populations during the whaling era and more recently by regulations on carcass management and disposal to abide by environmental health requirements. Here, we systematically review the scientific literature and gather data on cetacean strandings worldwide to: 1) identify the ecosystem services provided by stranded cetacean carcasses in the past and present; 2) estimate the density of cetacean strandings currently occurring in selected coastal areas around the globe, and analyse its association with human population density and regulations; and 3) identify and discuss the regulations and methods concerned with whale carcass disposal in specific regions of the world. Our literature review revealed that stranded cetacean carcasses have provided a rich and varied array of provisioning, regulating, cultural, and supporting ecosystem services to ancient and modern civilisations worldwide. Also, we found that the current density of stranded carcasses (mean: 0.090 strandings • year−1 • km−1; range: 0.001–0.978) and the disposal methods widely varied across the studied regions and countries. In addition, neither human population density nor the existence of regulations were good predictors of stranding densities. Finally, we provide recommendations for the future management of stranded cetacean carcasses, by identifying those disposal methods that minimize costs and maximize ecosystem functions and services. In particular, we encourage natural decomposition in situ whenever possible; otherwise, the present coastal management strategies could be improved by including zoning, seasonal use limitation and educational outreach depending upon the local scenario. Overall, further socio-ecological research is strongly needed to guide stranded cetacean carcass management towards enhancing the net benefits that humans and ecosystems gain from carcasses, especially considering that coastal areas become more populated, new disposal regulations are approved, and cetacean populations are recovering – and thus strandings may become more frequent.